Developing and Validating a Tool to Assess Young Children's Early Literacy Engagement. Issue 2 (June 2021) - Scull, Janet; Page, Jane; Cock, Megan L; Nguyen, Cuc; Murray, Lisa; Eadie, Patricia; Sparling, Joseph
There is growing recognition that literacy learning takes place in the years prior to formal schooling and that young children develop literacy-like behaviours through exposure to interactions in shared contexts in which literacy is a component. Despite this, there are few assessments that measure the very early literacy skills that children develop before 36 months of age. This article reports on the design and validation of a new instrument – the Early Literacy Engagement Assessment (ELEA). This tool was developed to provide insights into the impact of Conversational Reading, a key pedagogical strategy implemented at Families as First Teachers playgroups, on young children's early receptive and expressive vocabulary and literacy skills. The instrument was trialled with 104 children living in locations across Melbourne, Victoria, and 39 Aboriginal children living in remote communities in the Northern Territory. The trial process was undertaken in two phases: (1) a technical assessment to test item consistency, characteristics and placement and (2) concurrent validity testing against items from the Clinical Evaluation of Language Fundamentals Preschool-2 tool. The findings from the trial and validation process indicate that overall the ELEA discriminates well between children of high and low ability, and it is a useful tool in the authentic assessment of expressive and receptive vocabulary skills in young children.